Anqash qichwachaw hutitsinakuy - Julca Guerrero, Félix (2006)
This article explores and examines the system of proper names in Ancash Quechua. Historically, people of Quechua origin commonly had only one name, but since the arrival of the Spaniards this tradition began to change and Quechua names were sentenced to disappear. However, faced with the negative attitude of the peninsulars, the decrease and consequent absence of Quechua names, and as an action of linguistic and cultural resistance, the Quechua-speakers began to use a series of linguistic resources to name people. Some of these forms that are still very much in use in the Andean area of Ancash are: the progressive return to the use of proper names in Quechua, the use of Quechua hypocoristics with the intention of expressing affection and affection, and the use of Quechua nicknames and nicknames to express some ill-intentioned forms, ironies and euphemisms loaded with a touch of Andean affectivity and humor.